THE USE OF COLLABORATIVE WRITING TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Irwandi Irwandi (Linguistics and ELT Journal, 2015)
This study was carried out to find out about the use of collaborative writing technique to improve students ability in writing descriptive text at the second grade of SMPN 1 Praya in academic year 2015/2016. The total number of samples were 40 students, and they were divided into two groups. The first group was called the experimental group consisted of 20 students and the second group was called the control group consists of 20 students. The data of the study was collected by giving both of groups pre-test and the treatment just for the experimental group which was taught by using collaborative writing technique, and then at the last session of both groups was post-test with the same test items. After analyzing the data obtained, the researcher found that the use of collaborative writing technique affects writing a descriptive text. From the data analysis, the researcher found that the value of t-test was 6,3, while the value of t-table in df 38 were 2,024 for confidence level 0,05 (90%) and 2,71 for confidence level 0,01 (99%). It showed that the value of t-test is higher than the t-table. It is mean that the use of collaborative writing technique affects writing a descriptive text. So, the null hypothesis (Ho) was accepted because the use of collaborative writing technique affects writing descriptive text at the second grade of SMPN 1 Praya in Academic Year 2015- 2016.